Effects of Cognitive Control Exertion and Motor Coordination on Task Self-Efficacy and Muscular Endurance Performance in Children - Graham, Jeffrey D.; Li, Yao-Chuen; Bray, Steven R.; Cairney, John (Frontiers in Human Neuroscience, 2018)
Emerging research shows a strong connection between brain areas governing cognition and motor behavior. Yet, research investigating the negative aftereffects of cognitive control exertion on task performance has not considered the potential role of areas governing motor behavior. The present study investigated the effects of high cognitive control exertion on task self-efficacy and exercise performance in children. A secondary purpose was to investigate whether motor coordination influences the change in exercise performance differently following low versus high cognitive control exertion. Participants (N = 70) performed two isometric handgrip endurance trials separated by a Stroop task, which was either congruent (low cognitive control) or incongruent (high cognitive control). Motor coordination was assessed prior to the first endurance trial. Task self-efficacy for performing the second endurance trial was assessed following the Stroop task. Participants in the high cognitive control condition reported lower task self-efficacy and showed a reduction in endurance exercise performance. Task self-efficacy mediated the cognitive control – performance relationship. Participants scoring lower on motor coordination showed the greatest declines in exercise performance following high cognitive control, whereas motor coordination did not affect performance following low cognitive control. The results of this study provide evidence that task self-efficacy and exercise performance are also negatively affected in children following high cognitive control, and interestingly, these effects are exacerbated among those scoring lower in motor coordination. We recommend future research investigate motor coordination as a potential mechanism for the reductions in both cognitive and physical task performance following the prolonged exertion of high cognitive control.